(untitled) (The Journal of Plant Protection Sciences, 2022)
In the present study, the efficacy of different insecticidal treatment schedules against aphid and whitefly on brinjal was studied by conducting two field experiments at ’Adisaptagram Block Seed Farm, Hooghly, West Bengal, India in two consecutive kharif seasons i.e., 2010 and 2011. The experiment was laid in RBD with seven treatment schedules and three replications. Among all the treatments soil application of phorate at transplanting, followed by foliar spray with aceaphte, thiodicarb and Bacillus thuringiensis var. kurstaki at 50, 70 and 90 days after transplanting, respectively and seedling treatment with imidacloprid before transplanting, succeeded by foliar spray with imidacloprid, novaluron, B. thuringiensis var. kurstaki and novaluron at 30, 50, 70 and 90 days after transplanting were most effective in reducing the aphid and whitefly population over control during both the years of study. Consequently both the treatment schedules achieved maximum marketable fruits of brinjal as well as highest monetary return than the other treatments.